**Solution:**

We can write it as

= (x^{m – n})^{l}. (x^{n – 1})^{m}. (x^{1-m})^{n}

By further calculation

= (x)^{(m – n)l}. (x)^{(n – 1)m}. (x)^{(l – m)n}

= x^{ml – nl}. x^{nm – lm}. x^{ln – mn}

So we get

= x^{ml – nl + nm – lm + ln – mn}

= x^{0}

= 1

We can write it as

= (x^{a + b – c})^{a – b}. (x^{b + c – a})^{b – c}. (x^{c + a – b})^{c – a}

By further calculation

= x^{(a + b – c) (a – b)}. x^{(b + c – a) (b – c)}. x^{(c + a – b) (c – a)}

So we get

= x^{0}

= 1

**More Solutions:**

- Simplify the following: (i) (81/16)-3/4.
- Simplify the following : (i) (2a-3b2)3
- Simplify the following: (i) 3a/b-1 + 2b/a-1
- Simplify the following: (i) (8/125)-1/3
- Simplify the following : (i) (-1/27)-2/3
- Simplify the following Indices:
- Evaluate the following indices:
- Simplify the following:(i) (3×2)-3 × (x9)2/3
- Simplify the following: (i) (32)0 + 3-4 × 36 + (1/3)-2